Community Involvement Towards a Circular Economy: a Sociocultural Assessment of Projects and Interventions to Reduce Undifferentiated Waste - Bringsken, Beatriz Michelle; Loureiro, Isabel; Ribeiro, Carlos; Vilarinho, Cândida; Carvalho, Joana (European Journal of Sustainable Development, 2018)
In a Circular Economy, waste is a resource with potential to be valued. This concept idealized almost 30 years ago is still vague in its practical implementation process. This study evaluates from a social perspective the tendency to integrate resources into the waste management to answer the question: “How sociocultural perspectives on waste within a community could influence interventions and projects towards a circular economy?”. Therefore, organized communities in the municipality of Guimarães and the University of Minho (UMinho), in the north of Portugal, were chosen as case study and strategies were analysed. The first part of this study focuses on evaluating the impact of a community project known as ‘Brigada Verde’ implemented in about 20 parishes in Guimarães. The second part relates to assisting in the policymaking process of a Sustainability Plan at UMinho; and the final section assesses best-practices for waste created by agents who took initiative towards a Circular Economy. The research objective is to evaluate how community strategies effectively achieve results according to several indicators as values, changing behaviours and creating solutions to waste. Keywords: Sociology of Waste, Policymaking, Circular Economy, Best-practices benchmarking.